Digital Control in Value Chains: Challenges of Connectivity for East African Firms. (1st January 2018) - Foster, Christopher; Graham, Mark; Mann, Laura; Waema, Timothy; Friederici, Nicolas
Abstract: In recent years, Internet connectivity has greatly improved across the African continent. This article examines the consequences that this shift has had for East African firms that are part of global value chains (GVCs). Prior work yielded contradictory expectations: firms might benefit from connectivity through increased efficiencies and improved access to markets, although they might also be further marginalized through increasing control of lead firms. Drawing on extensive qualitative research in Kenya and Rwanda, including 264 interviews, we examine 3 sectors (tea, tourism, and business process outsourcing) exploring overarching, cross-cutting themes. The findings support more pessimistic expectations: small African producers are only thinly digitally integrated in GVCs. Moreover, shifting modes of value chain governance, supported by lead firms and facilitated by digital information platforms and data standards are leading to new challenges for firms looking to digitally integrate. Nevertheless, we also find examples in these sectors of opportunities where small firms are able to cater to emerging niche customers, and local or regional markets. Overall, the study shows that improving connectivity does not inherently benefit African firms in GVCs without support for complementary capacity and competitive advantages.